Antiviral Efficiency of Pulse UV Sterilization - Volodymyr Chumakov; Mykhailo Ostryzhnyi; Oksana Kharchenko; Krystina Naumenko; Svitlana Zagorodnya; Vasiliy Muraveinyk; Aleksandr Tarasevich (Research Advances in Microbiology and Biotechnology Vol. 6, 2023)
This chapter presents the results of an experimental study of the antiviral efficiency of a pulsed source of broadband UV radiation based on an open discharge in the atmosphere at the exit of an end-face plasma accelerator. The large-scale pandemic caused by the SARS-CoV-2 virus has largely updated research in the development and creation of methods and means of anti-epidemic protection of the population. The studies used influenza virus type A (H1N1) strain A / FM / 1/47, obtained from the collection of the State Institution of the Institute of Epidemiology and Infectious Diseases named after L.V. Gromashevsky NAMS of Ukraine. The virus was cultured in an MDCK cell culture and stored in aliquots at-70°C. An end-face plasma accelerator was used as a radiation source, which provides a power pulsed discharge in an open atmosphere. Within a short amount of time, the virus’s high efficiency of inactivation of its infectiousness was demonstrated. For the first time, it has been demonstrated that a viral infection may be 100% sterilised urgently. The effectiveness of pulse sterilisation can be determined using a model. The prospects for the application of pulse sterilization technology to combat coronavirus infection are considered.